PATIENTS' RIGHTS AND OBLIGATIONS IN THE PERSPECTIVE OF HEALTH LAW IN INDONESIA - Hotmaria Hertawaty Sijabat (Adisam Publisher, 2025)
This article discusses the important role of patients' rights and obligations in Indonesian health law. Patients' rights, such as obtaining correct information and safe healthcare services, as well as the obligation to comply with medical instructions, are regulated in law to ensure a good relationship between patients and medical personnel. Nonetheless, low public awareness and facility limitations often pose challenges in their implementation. Therefore, cooperation between the government, healthcare providers, and the public is needed to improve understanding and implementation of these rights and obligations. With the right steps, the implementation of patients' rights and obligations is expected to be more effective and have a positive impact on the healthcare system in Indonesia.